Simultaneous detection of vanilin and ascorbic acid on a platform modified with nickel tetraamine pthalocyanine nitrogen doped graphene - Maringo, Julius T. (Midlands State University, 2018)
An electrochemical sensor based on nickel tetraamine phthalocyanine and nitrogen doped grapheme oxide (NITAPC-NDGONS (mix)) nanoparticles was developed for the simultaneous electrocatalytic oxidation of vanillin and ascorbic acid. FTIR (Fourier Transimition Infrared), electrochemical impedance spectroscopy (EIS) and Bode plots were used in the characterization of the synthesized modifiers (NITAPC), (GONS-NITAPC) and NITAPC-NDGONS (mix)). Cyclic voltammetry, linear sweep, chronoamperometry and differential pulse voltammetry were used to assess the electrocatalytic efficiency towards oxidation of vanillin and ascorbic acid. …